The impact of team diversity on team performance - Boey, Lee Ping (2012)
Team diversity has often been labeled as a “double-edged sword” due to differing theoretical perspectives and contradictory findings. Hence, this study aims to find an integrative view regarding these contradictory empirical findings. The influence of age diversity, educational background diversity and extraversion on information sharing and team performance was examined with data from 34 employees in 12 natural work unit groups spanning 6 companies situated in Singapore. Contrary to our hypotheses, results showed that both age diversity and educational background diversity each have a positive relationship with information sharing. However, information sharing was also found to have a positive effect on team performance as expected. It is comforting to learn that age diversity, educational background diversity and information sharing can play a unique role in achieving better work performance. As such, organizations can look to achieving teams that are more effective with greater diversity in their teams.